2008
DOI: 10.1080/09588220801943718
|View full text |Cite
|
Sign up to set email alerts
|

Learners' and teachers' perspectives on language online

Abstract: This article examines the student and instructor satisfaction with the Language Online courses at Carnegie Mellon University from 2000-2002. These courses were designed with a hybrid format, including reduced face-to-face contact and online delivery of course materials. Quantitative and qualitative data were collected from students and instructors using surveys, interviews, and focus groups. Quantitative data from students indicates a trend of increasing satisfaction with the online courses compared with offli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 8 publications
9
56
1
1
Order By: Relevance
“…Just 6% of the students declared that the online teaching system was very useful. These results are contrary to the findings of the studies mentioned in the literature review part of our study as in all of them the learners are quite content with the online learning system (Allen, Bourhis, Burrell and Mabry , 2002;Murday , Ushida & Chenoweth, 2008;Kim, Liu and Bonk, 2005;Song, Singleton, Hill and Koh, 2004).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Just 6% of the students declared that the online teaching system was very useful. These results are contrary to the findings of the studies mentioned in the literature review part of our study as in all of them the learners are quite content with the online learning system (Allen, Bourhis, Burrell and Mabry , 2002;Murday , Ushida & Chenoweth, 2008;Kim, Liu and Bonk, 2005;Song, Singleton, Hill and Koh, 2004).…”
Section: Resultscontrasting
confidence: 99%
“…The learners had a positive attitude towards distance learning. Murday , Ushida & Chenoweth (2008) from Indiana University conducted a research on learners' perspectives on language online. Quantitative data from students indicates a trend of increasing satisfaction with the online courses compared with traditional courses.…”
Section: Studies On Distance Learningmentioning
confidence: 99%
“…Through managing this language learning environment, they had to construct favorable conditions for language acquisition, which in turn helped learners "develop learning strategies and become autonomous and confident learners, able to manage a language learning system which relies strongly on their ability to work independently" (ibid). Despite this clear change in participant roles, Bañados, like Murday et al (2006Murday et al ( , 2008, maintains that these findings support BL model implementation, as language learning was significantly improved.…”
Section: Blended Learning and Its Influence On Teaching Rolesmentioning
confidence: 92%
“…As mentioned, one significant aspect of teaching a BL course was training, since the technology that made such classes possible caused difficulties in teachers' lives whenever there were technical problems. Nevertheless, as Murday et al (2006Murday et al ( , 2008 note, such difficulties brought about a strong communal effort among teachers in coming to terms with managing the online component of the course, which was somewhat different from managing traditional FTF environments. Therefore, despite these issues, the blended program was evaluated as a positive experience; the problems faced during implementation were outweighed by the benefits in terms of learning and satisfaction.…”
Section: Blended Learning and Its Influence On Teaching Rolesmentioning
confidence: 99%
“…Thus previous studies on CALL evaluation have shown considerable interest in learners' and/or teachers' perceptions of English learning websites (Aly, 2008;Cheng, 2001;Hirata & Hirata, 2009;Kessler & Plakans, 2001;Kung & Chuo, 2002;M. Liu et al, 2008;Son, 2005Son, , 2008, the benefits and drawbacks of CALL materials/ programs, web-based language learning, and online language learning (Celik, 2012;Felix, 2001bFelix, , 2002Hughes, Mcavinia, & King, 2004;Murday, Ushida, & Chenoweth, 2008;Rosell-Aguilar, 2004;Wiebe & Kabata, 2010;F.-Y. Yang & Tsai, 2008), as well as learning autonomy in e-learning contexts (Chan & Kim, 2004;Lai & Gu, 2011).…”
Section: Significancementioning
confidence: 99%